Isolation and structural elucidation of bis-indole alkaloid and acyclic terpene from caulerpa racemosa (chlorophyta) and their antimicrobial, antioxidant, cytotoxic and their anti-inflammatory studies - Fitriyanti
Natural products from marine source have attracted our interest due to their unique chemical constituents. Genus of Caulerpa has been studied for their phytochemicals contents bioactivities. The aims of this research were to screen biological activity of C. racemosa through antimicrobial (disc diffusion method), antioxidant (total phenolic content, total flavonoid content and DPPH free radical scavenging assay), cytotoxicity and anti-inflammatory (MTT assay) properties, to isolate and elucidate the structure of compounds from C. racemosa, and to determine the biological properties of isolated compounds. The whole part of C. racemosa was extracted using Soxhlet extraction for 24 hours with n-hexane, dichloromethane and methanol, consecutively, to obtain crude extracts. Column chromatography technique was used to isolate the compounds using normal phase and chemical structures of isolated compounds were identified by spectroscopic techniques including ultraviolet (UV-Vis), infrared (IR), one and two dimensions of nuclear magnetic resonance (NMR) and mass spectroscopy (MS). The crude extracts showed no inhibition against Staphylococcus cereus, Bacillus aureus, Escherichia coli, and Pseudomonas aeruginosa. Dichloromethane extract of C. racemosa showed the highest total phenolic (102.35 ± 0.3 mg GAE/g of extract) and flavonoid content (200.34 ± 0.07 mg QAE/g of extract) followed by n-hexane and methanol extracts. Low activity of C. racemosa extracts were observed in scavenging free radical that were only 5.0% (n-hexane), 9.8% (dichloromethane), and 4.7% (methanol) at 5 mg/mL of concentration, and cytotoxicity against H1299, A549 and MCF7 for n-hexane (68.42%, 76.36% and 77.61%), dichloromethane (62.54%, 63.53%, and 67.16%) and methanol (66.08%, 65.50% and 67.17%), respectively at 100 μg/mL. The isolated compounds were characterized as dimethyl-2,12-dihydrocyclooctal[1,2-5,6]diindole-6,13-dicarboxylate that was known as Caulerpin, two new compounds, 4-phenyl-5,12-dihydroindolo[3,2]-carbazole and 3,9-dihydroxy-4,5,6,7,7,8,8,9-nonamethyl-3-propyldecan-one. The caulerpin exhibited a good inhibitory activity against A549 cell proliferation (41.60%) and a slight inflammatory activity against RAW 264.7 with the decreased of nitric oxide concentration from 32.71 to 29.079 μM.